Autism and culture: the effect on epidemiology and diagnosis at home and abroad - Grinker, Roy (Henry Stewart Talks, 2010)
International awareness, Autism prevalence worldwide, Autism and culture, Learning from schizophrenia studies, Developmental disorders and culture, The Diagnostic and Statistical Manual of Mental Disorders (DSM), Adoption of DSM and International Classification of Diseases (ICD), Cross-cultural comparisons, Importance of a meaningful diagnostic term, Social changes, The diagnostic net has widened, Autism spectrum disorders, Pervasive developmental disorders, Adults with autism, Traumatic brain injury and IDEA, Challenges to ASD surveillance, Prevalence and access to services, Disease or disability?, Language and diagnosis, Autism rights, Neurodiversity